Mengidentifikasi dan Memecahkan Masalah Pembelajaran yang Dihadapi Oleh Mahasiswa Melalui Strategi Lesson Study - Atti Herawati; Asih Wahyuni (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
Starting from the dissatisfaction with the outcomes of English learning in a subject matter, this study aims at investigating the main problems of students on learning in Research on ELT subject. In it, the writers find that students face difficulties in clustering their thought while learning. It can be seen from the results of evaluation given to the students. Woefully, it has not been identified yet since the lectures seem run smoothly through. Dealing with the problems identified, this study thus employs a lesson study towards sixth semester students of English Education Study Program in Bogor. The study covers four cycles in the implementation. The cycle then applies three stages; which are plan, do, and see. The data of this study are gained from the result of the individual post-test conducted after the topic was lectured. The data are also gained from the results of classroom observation, questionnaire distribution, and guided interview. First observation identifies that students are difficult to take a note from what the lecturer has explained. The students are rigid in clustering ideas from the materials driven. Some of them do a note in a limited handwriting. In the second classroom observation, lecturer chunks video learning into several segments. In doing so, it is intended to space the students for making a note easily. Having chucked the video learning throughout the activity, still, the students are unable to be forced out of shape. Limited number of students are making a note. In the third cycle, the lecturer provides a rubric for helping the students to analyse the video, still, they are unable to make an appropriate note taking. Thus, in the fourth cycle, the video is chunked into several segments. While watching the video, students are accompanied by a video observation rubric. Results based on the video observation rubric show that how students’ ability to make a note are influenced by guiding statements/questions provided on the rubric. From the results based on the four cycles of lesson study; thus, it can be concluded that students have difficulties in clustering ideas and making a note throughout the teaching and learning activity. Attempts have been made to solve the students’ problems of clustering ideas and making a note. The attempts to scaffold the students are providing a rubric and uttering guided questions while they are learning.